#### Answer

please see step-by-step

#### Work Step by Step

A recursion formula defines how to obtain the next term
if we know the preceding term(s).
So, instead of defining the terms as a function of n,
they are defined as a function of previous term(s).
The form is $a_{n+1}=$( expression involving $a_{1},...,a_{n})$
Example:
$\left\{\begin{array}{ll}
a_{1}=3 & \\
a_{n+1}=a_{n}+2, & n \geq 1
\end{array}\right.$
defines a sequence with terms
$a_{1}=3$
$a_{2}=3+2=5$
$a_{3}=5+2=7$
$... etc$
3, 5, 7, 9,...
The above sequence can be defined as as a function of n
by defining the general term with
$a_{n}=2n+1$